2023
DOI: 10.3390/molecules28062858
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Release of Methylglyoxal (MGO) from Honey and Honey-Based Formulations

Abstract: Methylglyoxal (MGO) is considered to be one of the vital components responsible for the anti-bacterial activity of Leptospermum spp. (Manuka) honey. While many studies have demonstrated a dose-dependent antibacterial activity for MGO in vitro, from a therapeutic viewpoint, it is also important to confirm its release from Manuka honey and also from Manuka honey-based formulations. This study is the first to report on the release profile of MGO from five commercial products containing Manuka honey using a Franz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Several non-peroxide components have been reported to contribute to the antibacterial activity of honey. The most extensively studied are methylglyoxal and methyl syringate which are found predominantly in Manuka honey (Johnston et al 2018, El-Senduny et al 2021, Hossain et al 2023). Honey also contains a diverse array of phytochemicals including polyphenols which are derived from the nectar of flowers (Mduda et al 2023c).…”
Section: Resultsmentioning
confidence: 99%
“…Several non-peroxide components have been reported to contribute to the antibacterial activity of honey. The most extensively studied are methylglyoxal and methyl syringate which are found predominantly in Manuka honey (Johnston et al 2018, El-Senduny et al 2021, Hossain et al 2023). Honey also contains a diverse array of phytochemicals including polyphenols which are derived from the nectar of flowers (Mduda et al 2023c).…”
Section: Resultsmentioning
confidence: 99%
“…honey was quantified for the formulations loaded with the WA Manuka honeys and New Zealand Manuka honey. MGO was quantified using a validated HPLC assay described by Hossain et al [ 45 ]. Studies have shown that high levels of MGO in Manuka honey stem from the presence of dihydroxyacetone (DHA) [ 46 , 47 , 48 ], identified as a direct precursor for MGO formation.…”
Section: Methodsmentioning
confidence: 99%
“…[1] Honey primarily consists of sugars (70-80 %), alongside water (about 17 %) and minor components, which make up approximately 3 % of honey's total mass. [2][3][4] The range of bioactivities recorded for different honeys, such as antibacterial, antioxidant, antifungal, antidiabetic and anti-inflammatory effects, are mainly related to the floral source and geographical origin of the honey, as well as its specific phytochemical profile, particularly its phenolic constituents, and physicochemical properties. [3,4] Clover honey is a unique type of honey produced from various species of the Trifolium genus, [5] which includes clovers and trefoil, which are low leguminous annual, biannual or perennial herbs, often with trifoliate leaves and dense white, yellow, red or purple flower heads.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The range of bioactivities recorded for different honeys, such as antibacterial, antioxidant, antifungal, antidiabetic and anti-inflammatory effects, are mainly related to the floral source and geographical origin of the honey, as well as its specific phytochemical profile, particularly its phenolic constituents, and physicochemical properties. [3,4] Clover honey is a unique type of honey produced from various species of the Trifolium genus, [5] which includes clovers and trefoil, which are low leguminous annual, biannual or perennial herbs, often with trifoliate leaves and dense white, yellow, red or purple flower heads. [5] The word clover is likely derived from the old German word Klaiwaz, which refers to the stickiness of the sap of clover or the honey produced from the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation